Extreme animal rumble : 5 books in 1! - Pallotta, Jerry (Pallotta, Jerry. Who would win?, 2021)
What would happen if sixteen sharks met in a tournament? What if the jungle's fiercest creatures battled it out? Which dinosaur is the strongest of them all?